ANALYSIS OF POTENTIAL OCCUPATIONAL ACCIDENTS USING THE HAZOP METHOD IN POST-HARVEST SHARK FIN PROCESSING IN TANJUNG LUAR FISH LANDING BASE - Agustian, Yoppie; Riyanto, Mochammad; Purwangka, Fis; Prasetyo, Andhika Prima (Jurnal Penelitian Perikanan Laut (Albacore), 2025)
Occupational Health and Safety (OHS) in the fishing industry is often overlooked, despite the extremely high potential for work-related accidents. This study aims to analyze the risks during the post-harvest process of shark fins at Tanjung Luar Fishing Port and UD Mamenasae using the Hazard and Operability Study (HAZOP) method. The results indicate that nearly all activities, especially cargo hold unloading, transfer, transport, identification, shark cutting, and fin drying, have a high-risk potential for accidents such as falls/slips, musculoskeletal complaints, cuts, and sunburn. Some processes, including transportation to collectors, storage, sorting, and packaging, carry a moderate risk of concussion or respiratory disorders. Furthermore, all stages present a low risk of bacterial infectious diseases. The primary hazards identified include slippery floors, non-ergonomic work postures, sharp objects, the absence of Personal Protective Equipment (PPE), sun exposure, and a lack of railings. As a mitigative measure, temporary actions such as improved hygiene, provision of PPE, ergonomic improvements, and education are highly recommended to reduce potential hazards and enhance workplace safety. Key words: HAZOP, occupational safety, post-harvest, risk analysis, shark fin